2018
DOI: 10.1111/jcmm.13697
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection of ischaemic preconditioning is associated with inhibition of translocation of MLKL within the plasma membrane

Abstract: Necroptosis, a form of cell loss involving the RIP1‐RIP3‐MLKL axis, has been identified in cardiac pathologies while its inhibition is cardioprotective. We investigated whether the improvement of heart function because of ischaemic preconditioning is associated with mitigation of necroptotic signaling, and these effects were compared with a pharmacological antinecroptotic approach targeting RIP1. Langendorff‐perfused rat hearts were subjected to ischaemic preconditioning with or without a RIP1 inhibitor (Nec‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
(85 reference statements)
0
24
0
Order By: Relevance
“…Nec-1s has not been studied in clinical trials so far; only in vitro and ex vivo animal studies have been performed with this agent [ 10 , 15 , 16 , 17 ]. Likewise, according to our best knowledge there are no in vivo animal studies investigating the anti-necroptotic effects of Nec-1s.…”
Section: Resultsmentioning
confidence: 99%
“…Nec-1s has not been studied in clinical trials so far; only in vitro and ex vivo animal studies have been performed with this agent [ 10 , 15 , 16 , 17 ]. Likewise, according to our best knowledge there are no in vivo animal studies investigating the anti-necroptotic effects of Nec-1s.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether all cell death mechanisms in MI affect subsequent cardiac remodeling processes remains largely unknown. Recent studies have suggested that necroptosis inhibition is involved in cardioprotection of ischemic preconditioning and is associated with inhibition of the translocation of MLKL within the plasma membrane 38 . Very recently, it was shown that Ripk3 promotes endoplasmic reticulum (ER) stress-induced necroptosis via the calcium overload/XO/ROS/mPTP opening axis in cardiac IR injury 33 …”
Section: Discussionmentioning
confidence: 99%
“…TBARS levels were analyzed, as a marker of oxidative stress and lipoperoxidation, according to Shlafer and Shepard (1984) [ 38 ] with modifications [ 39 ]. 40 µL of tissue homogenates and 40 µL of 20% trichloroacetic acid solution were mixed with a 320 µL of TBARS reagent (37 mmol/L C4H 4 N 2 O 2 S, 500 mmol/L NaOH, 15% v / v CH 3 COOH) and incubated for 70 min at 100 °C.…”
Section: Methodsmentioning
confidence: 99%
“…TBARS levels were analyzed, as a marker of oxidative stress and lipoperoxidation, according to Shlafer and Shepard (1984) [38] with modifications [39]. 40 µL of tissue homogenates and 40 µL of 20% trichloroacetic acid solution were mixed with a 320 µL of TBARS reagent (37 mmol/L C4H 4 N 2 O 2 S, 500 mmol/L NaOH, 15% v/v CH 3 COOH) and incubated for 70 min at 100 • C. Subsequently, the mixture was cooled on ice for 10 min, pipetted into another tube with a mixture of n-butanol and pyridine (14:1, v/v), and centrifuged 10 min at 5000× g. The organic phase was used for measurement of absorbance at 535 nm by Synergy H1 Hybrid Multi-Mode Microplate Reader (Biotek, Vermont, USA).…”
Section: Measurement Of Lipoperoxidation By Thiobarbituric Acid Reactmentioning
confidence: 99%